Polymorphisms of HLA‐DP are associated with response to peginterferon in Caucasian patients with chronic hepatitis B. Issue 7 (11th August 2014) - Brouwer, W. P.; Sonneveld, M. J.; Tabak, F.; Simon, K.; Cakaloglu, Y.; Akarca, U. S.; Zeuzem, S.; Ferenci, P.; Heathcote, J. E.; de Knegt, R. J.; Boonstra, A.; Hansen, B. E.; et al.
Summary Background Polymorphisms of the HLA‐DP gene are associated with the natural clearance of the hepatitis B virus in Asian patients. Aim To investigate the association of HLA‐DP polymorphisms with response to peginterferon (PEG‐IFN) in Caucasian chronic hepatitis B (CHB) patients. Methods We studied 262 Caucasian chronic hepatitis B patients infected with HBV genotype A or D, treated with PEG‐IFN for 1 year in two randomised controlled trials (HBV 99‐01 and PARC study). Response was defined as an HBV DNA <2000 IU/mL at 6 months post‐treatment. Variations at HLA‐DPA1 and HLA‐DPB1 were genotyped. Results Of the 262 patients, 58% was HBeAg‐positive and HBV genotype A and D was observed in 32% and 68%, respectively. At 6 months post‐treatment, 57 (22%) patients had achieved an HBV DNA <2000 IU/mL. HLA‐DPB1 was independently associated with virological response [adjusted odds ratio (OR) 1.8, 95% confidence interval (CI):1.1–3.0, P = 0.025], and with an undetectable HBV DNA (adjusted OR 2.4 95% CI: 1.2–4.7, P = 0.015) when adjusted for HBeAg status and other known response modifiers. In HBeAg‐positive patients, combined HBeAg seroconversion with HBV DNA <2000 IU/mL was increasingly observed with each addition of an HLA‐DPB1 G‐allele (adjusted OR 2.7, 95% CI: 1.2–5.9, P = 0.012). Furthermore, HLA‐DPA1 and HLA‐DPB1 haplotype block GG showed comparable results for virological and combined response. Conclusion In this large cohort of Caucasian chronic hepatitis B patients infected with HBV genotypes A or D, polymorphisms of HLA‐DP are independently associated with both virological and serological response to PEG‐IFN therapy at 6 months post‐treatment.